PENGARUH EFIKASI DIRI DAN MOTIVASI KERJA TERHADAP KINERJA GURU MADRASAH IBTIDAIYAH KECAMATAN NATAR - Rizka Septia; Bambang Sri Anggoro; Eti Hadiati (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of self-efficacy and work motivation on the performance of teachers at private Madrasah Ibtidaiyah. Teacher performance is an important factor in determining the quality of learning and educational outcomes, which is influenced not only by competence but also by psychological and motivational factors. This research employed a quantitative approach using a survey method. The population consisted of teachers from private Madrasah Ibtidaiyah in Natar District, with the sample selected through an appropriate sampling technique. Data were collected using validated and reliable questionnaires and analyzed using simple and multiple linear regression. The results indicate that self-efficacy has a significant effect on teacher performance. In addition, work motivation also significantly influences teacher performance. Simultaneously, self-efficacy and work motivation contribute significantly to improving teacher performance. The novelty of this study lies in providing empirical evidence on the integrated role of psychological and motivational factors in enhancing teacher performance in private Madrasah Ibtidaiyah.